Urgensi Administrasi Kependudukan Desa Lau Tawar Kabupaten Dairi Perspektf UU No. 23 Tahun 2006 - Isnawati Sembiring; Zulfan Efendi Hasibuan (Jurnal El-Thawalib, 2023)
The problem in this research is how is the role of the Lau Tawar Village government in increasing awareness of the orderly population administration and civil registration in Lau Tawar Village, Tanah Pinem District, Dairi Regency. Because if you look at it, there are still many people in Lau Tawar Village who don't care about their population administration.  Based on the Law of the Republic of Indonesia Number 23 of 2006 concerning the State Population Administration, it is obligated to provide protection and acknowledgment of the determination of personal status and legal status of every demographic and important event experienced by residents who are inside or outside the territory of the Republic of Indonesia.The purpose of this study is to analyze and describe how the role of the Lau Tawar Village government in increasing awareness of the orderly population administration and civil registration in Lau Tawar Village.  and civil registration in Lau Tawar Village.  The research method used by the researcher in this research is a sociological juridical approach.  The data collection instruments used in this study consisted of interviews, observations, and documentation. The results of this study are the Lau Tawar Village government issued an appeal to the community, came directly to the house, provided a wifi network, printer and laptop. Factors supporting the orderly population administration are the availability of wifi at the village office and a mini library where data is stored. Inhibiting factors are human resources that are still lacking, lack of discipline in the village apparatus, low public awareness, and inadequate facilities.